A desire called America : biopolitics, utopia, and the literary commons - Haynes, Christian P. (Fordham University Press, 2019)
Presents interpretations of American literature and politics, focusing on the work of Walt Whitman, Emily Dickinson, William S. Burroughs, and Thomas Pynchon. Analyzes how literary texts imagine America in utopian terms, contrasting American exceptionalism to non-capitalist visions of the American future.